Problematika Hukuman Mati di Indonesia dalam Perspektif Hukum Pidana dan Hak Asasi Manusia - Ahmad Husairi; Devrian Ali Putra; Nerisma Eka Putri; Sarah Nur Izzati; Kurnia Saputri (Fakultas Hukum Universitas Islam Indonesia, 2024)
In this era of reform, the death penalty remains a highly controversial issue and a matter of serious concern, prompting various approaches from legal experts and practitioners. Decisions to execute the death penalty for certain criminals are influenced by social initiatives and law enforcement efforts aimed at enhancing social welfare. Regarding the death penalty, there is a stigma that generates both pro and con opinions, related to the concept and realization of human rights. Therefore, researchers are interested in delving deeper into the issue of the death penalty in Indonesia from the perspectives of criminal law and human rights.In this study, researchers employ a normative juridical method, focusing on specific subjects for analysis, namely conducting regulations-based analysis using library research. The theory of punishment is used as a theoretical framework, leading to findings that the death penalty fundamentally entails depriving someone of their right to life and causing physical suffering, which contradicts Article 6(1) of the International Covenant on Civil and Political Rights and Article 3 of the Universal Declaration of Human Rights, as well as the shift from classical criminal justice systems focused on retributive justice to modern criminal justice systems oriented towards collective, restorative, and rehabilitative justice. The existence of the death penalty is considered a violation of an individual's right to life, as this right is deemed a gift that must be respected. Article 1 of Law Number 39 of 1999 concerning Human Rights, which acknowledges the rights of every individual in their entirety, affirms that human rights exist in Indonesia.